Straightforward Synthesis of Unnatural α,α-Disubstituted α-Amino Acid Derivatives Using Readily Accessible Building Blocks - Tomohara, Keisuke; Nose, Takeru; Nambu, Hisanori (Synlett, 2025)
Unnatural α,α-disubstituted α-amino acids have played a privileged role in drug discovery campaigns, and the development of their efficient synthetic methods has thus received continuous attention. This account describes our originally developed synthetic methods to obtain α,α-disubstituted α-amino acid derivatives using readily accessible building blocks.1 Introduction2 Asymmetric Synthesis of α,α-Disubstituted α-Aryl α-Amino Acid Derivatives via ‘Memory of Chirality’3 Synthesis of Natural-Product-Derived α,α-Disubstituted α-Amino Acid Derivatives by Chemical Engineering of Natural Product Extracts4 One-Pot Synthesis of α,α-Disubstituted α-Amino Acid Derivatives by Ammonia-Ugi Reaction5 Conclusions
Keywords: α,α-disubstituted α-amino acid; memory of chirality; Bucherer–Bergs reaction; Ugi reaction; ammonia-Ugi reaction; natural product extract